COMPARISON OF RESEARCH LIBRARIES STAFF IN VOLODYMYR DAHL EUNU IN 2002 AND 2012 (SCIENTIFIC LIBRARY - 90 YEARS) - Scherbyna, Klavdiia I. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
This comparative qualification characteristic of Scientific Library staff for the past 10 years is presented: the total number of employees by level of education, work experience in a library.